Characterization of UC781-Tenofovir Combination Gel Products for HIV-1 Infection Prevention in an Ex Vivo Ectocervical Model - Cost, Marilyn (American Society for Microbiology, 2012)
HIV continues to be a problem worldwide. Topical vaginal microbicides represent one option being evaluated to stop the spread of HIV. With drug candidates that have a specific action against HIV now being studied, it is important that, when appropriate and based on the mechanism of action, the drug permeates the tissue so that it can be delivered to specific targets which reside there. Novel formulations of the nucleotide reverse transcriptase inhibitor tenofovir (TFV) and the nonnucleoside reverse transcriptase inhibitor UC781 have been developed and evaluated here. Gels with three distinct rheological properties were prepared. The three gels released both UC781 and TFV under in vitro conditions at concentrations equal to or above the reported 50% effective concentrations (EC(50)s). The drug concentrations in ectocervical tissues were well in excess of the reported EC(50)s. The gels maintain ectocervical viability and prevent infection of ectocervical explants after a HIV-1 challenge. This study successfully demonstrates the feasibility of using this novel combination of antiretroviral agents in an aqueous gel as an HIV infection preventative.